Perinatal practical guidelines on COVID-19: what one should know to reduce the risk - Jelly, Prasuna; Sharma, Meenakshi; ., Gunjot (International Journal Of Community Medicine And Public Health, 2020)
Risk of COVID-19 in pregnant woman is the same as that in the general population but as pregnancy is a state of immunosuppression along with other physiological respiratory and immune changes. A pregnant woman might show more severe symptoms of COVID-19 infection. Health care employees should be permitted to meet pregnant women through managed home visits and with help of teleconsultations. Mothers should follow meticulous hand hygiene, respiratory etiquettes and social distancing because they have key role in restricting spread of infection. Protein rich diet, vitamin C, vitamin D, zinc, calcium, iron and folic acid are very necessary components to be consumed by antenatal woman. It may help to protect mother and baby by having certain vaccines during pregnancy such as the influenza, tetanus and Tdap vaccines. Pregnant women with major risk of exposure/COVID-19 symptoms and no emergency obstetric issues should be stated for testing outside the hospital. Pregnant women without urgent obstetric issues awaiting results should stay at home to self-isolate. Those with emergency obstetric issues should be managed in labour room devoted to COVID-19 patients. Mode of delivery depends upon obstetrical indication and health condition of mother. Regular assessment of respiratory condition should be done during labour along with continuous electronic foetal monitoring. The WHO encourage mothers with COVID-19 to hold and breastfeed their babies because close connection is essential for new-born but to reduce risk of transmission temporary separation of new born from mother with confirmed or suspected COVID-19 is considered strongly.